2008
DOI: 10.1007/s12149-008-0143-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of norcholesterol scintigraphy, CT attenuation value, and chemical-shift MR imaging for characterizing adrenal adenomas

Abstract: The norcholesterol uptake rate was reliable for characterization of adenomas among adrenal masses of >or=2.0 cm. CT attenuation value and MR suppression index were well correlated with each other, and were useful regardless of mass size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…in patients with adrenal masses to identify cortisolproducing adenomas including SCS, but these studies have been performed on relatively small numbers of subjects [16][17][18]. To date, no study has examined which adrenal uptake rate on ACS (the tumor or nontumor side) reflects the cortisol production ability of the adenoma.…”
Section: Fig 2 Correlation Of Tumor Size With Uptake Rates On the Afmentioning
confidence: 99%
“…in patients with adrenal masses to identify cortisolproducing adenomas including SCS, but these studies have been performed on relatively small numbers of subjects [16][17][18]. To date, no study has examined which adrenal uptake rate on ACS (the tumor or nontumor side) reflects the cortisol production ability of the adenoma.…”
Section: Fig 2 Correlation Of Tumor Size With Uptake Rates On the Afmentioning
confidence: 99%
“…In contrast, nonadenomas do not show signal loss on out-of-phase imaging (23). Recent studies have shown that 60 to 89 percent of lesions measuring between 10 and 30 HU on unenhanced CT can be characterized using chemical shift MRI (24,25).…”
Section: Tissues Characterizationmentioning
confidence: 99%
“…In recent years, particularly with the widespread use of ultrasonography (US), computed tomography (CT) and magnetic resonance imaging (MRI), there has been a marked increase in the overall incidence of incidentalomas. Adrenal incidentalomas should primarily be assessed in terms of the lesion's hormonal activity and malignant potential (5,6).…”
Section: Introductionmentioning
confidence: 99%